Validation of the Integrated Model of Health Literacy in Patients With Breast Cancer. Issue 6 (November 2018) - Hou, Wen-Hsuan; Huang, Yi-Jing; Lee, Yen; Chen, Cheng-Te; Lin, Gong-Hong; Hsieh, Ching-Lin
Abstract : Background: Health literacy (HL) enables patients with breast cancer to actively participate in health decisions and promote positive health outcomes. The Integrated Model of Health Literacy (IMHL), defined as the personal, situational, and societal/environmental factors that predict the level of HL that can influence health outcomes, incorporates the concepts, determinants, and consequences of HL. Objective: The aim of this study was to examine the mechanisms and completeness of the IMHL in patients with breast cancer. Methods: Five hundred eleven Taiwanese patients were prospectively recruited. We conducted structural equation modeling to confirm and modify the predictive pathways linking the HL-related factors in the IMHL. Results: Results on a total of 511 breast cancer patients showed good model-data fit. An alternative model revealed better fit with 2 pathways added from cancer stage to self-rated health and from cancer duration to shared decision making. Both the original model and alternative model modification revealed that only personal determinants (age, education, cancer stage, and duration) and not situational determinants (marital status) or social/environmental determinants (residence and occupation) could significantly predict the 3 domains of HL. Theorized consequences of HL were significantly influenced by HL in both models. Conclusions: Our results partially support the relationships proposed in the IMHL for patients with breast cancer as only personal determinants significantly predicted HL. Implications for Practice: Understanding the predictive pathways of the integrated HL model could help clinicians to tailor HL interventions using a patient's personal determinants to facilitate participation in decision making and promote health for breast cancer patients.